Forecasting the impact of storm episodes on beaches: present limitations - Oliveira, F. S. B. F. (2015)
The application of credible morphodynamic forecast models to provide evidence-based information for coastal managers making decisions for re-profiling the beach and thus increase coastal resilience by restoring the sediment balance and providing space for coastal processes is a relevant issue since the future risk of coastal storm impacts is likely to increase. The study exposes the practical limitations and inevitable uncertainties found in the application of two state-of-the-art process-based morphodynamic numerical models to an Atlantic urban sandy beach under extreme wave energy and surge conditions. The erosion of the foreshore and backshore of this particular beach was characterised as function of the intensity and duration of the hydrodynamic forcing parameters. The models performance was evaluated and compared. A major conclusion achieved was that in order to obtain reliable simulations of the morphodynamics during high energy coastal events it is necessary to further develop and apply non-intrusive monitoring techniques, which enable accurate monitoring in such adverse environments, to capture the physics in those conditions and load correctly the numerical models. There is an urgent need to overcome the present limitation in order to achieve a higher level of reliability in beach erosion impact forecasts.